2004
DOI: 10.1117/12.545180
|View full text |Cite
|
Sign up to set email alerts
|

Planar waveguide microlenses for nonblocking photonic switches and optical interconnects

Abstract: Different types of planar waveguide microlenses are fabricated with planar lightwave circuit technologies from a variety of optical materials such as silica, photo-definable epoxy resins, and a number of other optical polymers. Hybrid microlenses are also fabricated in which the base of the lens, with a double concave gap, is formed from silica and the gap is filled with an optical polymer. The optimized lens structures provide the maximum coupling efficiencies between the input and output channels at distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The double lens gaps are filled with Cytop from Asahi Glass Company. An extensive study of the single and double lens properties has been reported previously [10]. The studies demonstrated that the planar waveguide microlenses collimated under specifically designed conditions the light beams with widths less than 400-500 m that can propagate in slab waveguides up to 10 cm without increase of the beam width.…”
Section: Th International Ceramics Congressmentioning
confidence: 96%
See 1 more Smart Citation
“…The double lens gaps are filled with Cytop from Asahi Glass Company. An extensive study of the single and double lens properties has been reported previously [10]. The studies demonstrated that the planar waveguide microlenses collimated under specifically designed conditions the light beams with widths less than 400-500 m that can propagate in slab waveguides up to 10 cm without increase of the beam width.…”
Section: Th International Ceramics Congressmentioning
confidence: 96%
“…In addition, the polymer gap filling decreases the vertical light divergence in the gaps. Several optical materials, including silica and a number of polymers, have been tested for the microlens applications [11]. Microlenses fabricated in silica-on-silicon technology demonstrate the best results for the single mode applications at 1550 nm wavelength ( ).…”
Section: Th International Ceramics Congressmentioning
confidence: 99%
“…1 and 2 can easily include multi-layer structures with vertical and lateral mirrors or waveguide bends so that 3D routing can be realized [7]. Alternative non-blocking OI routing architectures can also be used instead of regular channel waveguides [8].…”
Section: Figure 1 Optical Interconnect Module With Optical Jumpersmentioning
confidence: 99%